Productivity characteristics of endive as a function of spacing - Castoldi, R. (2012)
Endive (Cichorium intybus) is one of the vegetables least studied in Brazil with respect to the behavior of the most commercialized cultivars, but it is known that the number of plants per area is one of the factors that most influences the productivity of various crops. Thus, the objective of this work was to evaluate the behavior of endive using four spacings between rows and five spacings between plants, in the region of Jaboticabal-SP. The experiment was conducted in the field in the period of August 12, 2008 to November 6, 2008, in the experimental area of the Sector of Vegetable Crops and Aromatic-Medicinal Plants, Department of Crop Sciences, School of Agricultural and Veterinary Sciences - UNESP-FCAV. The experimental design utilized was a randomized block design with a 4 × 5 factorial scheme, i.e., four spacings between rows (0.15, 0.20, 0.25 and 0.30 m) and five spacings between plants (0.10, 0.15, 0.20, 0.25 and 0.30 m), with three repetitions. The endive cultivar studied was 'Pão-de-Acucar', obtained from the company Tecnoseed. Seedlings were established utilizing the sowing system in 200-cell Styrofoam trays containing the substrate Plantmax Vegetables® HA. The seedlings were transplanted at 37 days after planting. After harvesting, the following characteristics were determined: height (cm), diameter of the plant in rows (cm), diameter of the plant in between rows (cm), number of leaves, fresh weight (g) and total estimated productivity (t/ha). There were no interactions between the factors studied. Based on the data, we conclude that spacings of 0.15 m between rows and of 0.15 m between plants produce plants of higher quality and with greater productivity.